Properties of Components with Incrementally Formed Gears - Sebastian Wernicke; Peter Sieczkarek; Soeren Gies; A. Erman Tekkaya (Metals, 2019)
The process class of sheet-bulk metal forming (SBMF) involves several advantages for the manufacture of functional components. Its incremental variant (iSBMF) enables a very flexible dimensioning of components. To treat the unfavorable manufacturing time of the incremental approach, this investigation is focused on an alternative process route using rotating forming tools, which decrease the process time significantly. After an analysis of the mechanical properties as well as the micro- and macroscopic surface quality, a quasi-static benchmark test was performed. Normalized by the weight of the component, gears manufactured by iSBMF and BS600 steel presented the same load capacity as gears manufactured by blanking with subsequent hardening. Here, using innovative high strength steels with a significant strain hardening behavior like high manganese steels enables for weight-reduced gears.